2020
DOI: 10.1021/acs.joc.0c01818
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Hydroacylation of Alkenes by Directly Using Acyl Oximes

Abstract: Acyl oximes are directly used as the acyl radical precursors in the hydroacylation reactions for the first time. In this work, acyl radicals can be effectively generated via β-scission of a phosphoranyl radical under photocatalytic conditions. As a result, the hydroacylation of alkenes triggered by the resulting acyl radicals leads to facile syntheses of a range of valuable ketones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 51 publications
0
12
1
Order By: Relevance
“…Acyl oxime esters could be reduced through single electron transfer in the presence of photocatalyst to yield highly reactive iminyl radicals, which underwent β‐C−C bond fragmentation to disconnect acyl radicals from iminyl radicals through elimination of a nitrile molecule (Scheme 1c). The resulting acyl radicals could be coupled with a wide range of radical acceptors, including alkenes, [15a–c] aromatic rings, [15d] and alkynes [15e–g] . For example, Wu and co‐workers reported a photocatalytic acyl radical cascade reaction between acyl oxime esters with acrylamides and styrenes, respectively [15a] .…”
Section: Methodsmentioning
confidence: 99%
“…Acyl oxime esters could be reduced through single electron transfer in the presence of photocatalyst to yield highly reactive iminyl radicals, which underwent β‐C−C bond fragmentation to disconnect acyl radicals from iminyl radicals through elimination of a nitrile molecule (Scheme 1c). The resulting acyl radicals could be coupled with a wide range of radical acceptors, including alkenes, [15a–c] aromatic rings, [15d] and alkynes [15e–g] . For example, Wu and co‐workers reported a photocatalytic acyl radical cascade reaction between acyl oxime esters with acrylamides and styrenes, respectively [15a] .…”
Section: Methodsmentioning
confidence: 99%
“…For example, Xiao [4] and other chemists [5,7–8] have developed a series of ring‐opening of cycloketone oxime derivatives via NCR strategies. As shown in Scheme 1, Chen (path I), [11a] Wu (path II), [11b] Yang (path III), [11c] and Wu's groups (path IV) [11d] have developed NCR mediated cleavage of carbon‐carbon single bonds in acyl oxime derivatives. In these methods, acyl oxime esters were used as acyl precursors to reat with carbon‐carbon double bonds.…”
Section: Methodsmentioning
confidence: 99%
“…[75] Recently Xiang and co-authors reported the hydroacylation of alkenes 154 using acyloximes 153 as an acylating source under photocatalytic conditions, and it was proposed that phosphoranylradical is a key intermediate for acylation reaction (Scheme 40). [76] 3. Non-Carbonyl Derived Acylating Agents…”
Section: Oximesmentioning
confidence: 99%